The Importance of Building a Digital Business Startup in College - Ankur Singh Bist (Startupreneur Business Digital (SABDA Journal), 2023)
Indonesia has enough established startups for them to become popular in business incubators that accept college or university students. This is because aspiring entrepreneurs who have business ideas are given access to the incubation concept and program. As a result, study was done to find out how business incubators help colleges create firms. However, there are barriers to developing businesses, including limited technology, management, and leadership. A qualitative methodology was used to carry out the study at Raharja University's Alphabet Incubator. Utilizing an observational research approach and a literature review to gather data with the goal of streamlining the procedure, It is clear that the government supports business incubators in creating startups and utilizing technology to expand businesses. The goal of the research is to boost creativity or innovation in creating successful new companies in higher education. seen from students making use of the Alphabet Incubator's resources to create small enterprises in the digital sector and expand the workforce.